Especialização fisiológica de Puccinia triticina, agressividade e sensibilidade de raças a fungicidas - Bianchin, Vânia (2011)
Wheat (Triticum aestivum L.) is one of the most important crops in the world. Brazil is seeking self-sufficiency in wheat production and the employed technologies in farming are key factors to increase productivity. Several diseases can reduce wheat grain yield and leaf rust caused by Puccinia triticina Eriks. is one of the most important. The primary management of this disease is the development of resistant cultivars and chemical control. The fungus shows a large variability, resulting in the selection of new races throughout the years. Triazole (IDM) and strobilurin (IQE) are the only two chemical groups of fungicides recommended to control leaf rust. In 2007 was reported by the first time in Brazil, sensitivity reduction for MDP-MR, MR-MDT, MDK-MR-HT and MFH races of P. triticina. Aiming to evaluate whether the new identified new races in 2008 (TDP-MR, TPT-HT e TDP-HR) and 2009 (MDP-MR 4002S B58 4002S) remain with altered sensitivity in addition to the old races. Sensitivity of the new race SNJ-RR was compared to pattern-sensitive MCG MN. Inhibitory concentration (IC50) of triazole fungicides (IDMs), and tebuconazole cyproconazole and strobilurin (IQEs), azoxystrobin and pyraclostrobin preventive and curative applied were determined. Races SNJ-RR and MCG-MN showed greater sensitivity to fungicides and races TDP-HR and M (F) MT-DP (R) showed the greatest reductions in sensitivity totebuconazole and cyproconazole fungicides. It was also shown no sensitivity shift during the wheat development. In other tests it was possible to study the contact action of fungicides (triazoles and strobilurin) on the P. triticina uredospores germination. None of the applied fungicides inhibited germination efficiently through contact action. On comparative epidemiology, significant differences were found among races in all aspects analyzed. Races SNJ-RR-MN and MCG showed low sporulation rate, greater latency period. Tebuconazole fungicide was efficient to control the sensitive B34 race. Spores germination inhibition by light was greater in race B34 than for B55 4002S. The optimum temperature for spores germination in the presence of light for the race B55 4002S was 18.5°C, and in the dark 8.9°C, while for B34 was 16.2°C and 10.8°C, respectively